2015
DOI: 10.1177/1947603515594453
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Toxicity of Local Anesthetics and Corticosteroids on Chondrocyte and Synoviocyte Viability and Metabolism

Abstract: Objective:There is growing concern that intra-articular injection of local anesthetic and/or corticosteroids may cause significant morbidity, including potential toxicity to chondrocytes and synoviocytes, after even a single exposure. We demonstrate that full thickness canine chondral and synovial samples exposed to various local anesthetics and corticosteroids exhibit decreased loss of cell viability compared with prior in vitro studies using monolayer culture, due to the protective effects of intact extracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 21 publications
2
58
2
2
Order By: Relevance
“…2,3 This latter strategy may be preferable where characteristics of neuropathic pain are present, as well as to avoid concerns of chondrotoxicity from repeated intraarticular injections. 11,12 The ESP block was originally described for management of thoracic pain with injection at the T5 transverse process. [4][5][6] Its therapeutic effect is attributed to the cranial-caudal spread of local anesthetic over multiple vertebral levels in the musculofascial plane deep to the erector spinae muscle, accompanied by diffusion anteriorly into the contiguous paravertebral and intercostal spaces, where the local anesthetic then acts on the ventral and dorsal rami of spinal nerves.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 This latter strategy may be preferable where characteristics of neuropathic pain are present, as well as to avoid concerns of chondrotoxicity from repeated intraarticular injections. 11,12 The ESP block was originally described for management of thoracic pain with injection at the T5 transverse process. [4][5][6] Its therapeutic effect is attributed to the cranial-caudal spread of local anesthetic over multiple vertebral levels in the musculofascial plane deep to the erector spinae muscle, accompanied by diffusion anteriorly into the contiguous paravertebral and intercostal spaces, where the local anesthetic then acts on the ventral and dorsal rami of spinal nerves.…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrates that bupivacaine at a concentration of 0.22% is harmful for articular equine synoviocytes but its negative effects are less pronounced on chondrocytes. A protective effect from the existence of intact extracellular matrix on chondrocytes from the cartilage explant has been previously suggested [ 6 , 14 ], although this was recently questioned on an experimental canine model [ 10 ]. Local anaesthetics have drug-, dose- and time-dependent cytotoxic effects [ 5 , 10 , 35 – 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A protective effect from the existence of intact extracellular matrix on chondrocytes from the cartilage explant has been previously suggested [ 6 , 14 ], although this was recently questioned on an experimental canine model [ 10 ]. Local anaesthetics have drug-, dose- and time-dependent cytotoxic effects [ 5 , 10 , 35 – 37 ]. Bupivacaine 0.0625% did not cause cell death in canine cartilage and synovium explants [ 10 ] and varying toxicity has been observed for bupivacaine concentrations in the range of 0.125–0.25% [ 2 , 5 , 10 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence is lacking on additional benefits of LA on outcomes (Galloway and Bukhari ; Smith, ), and there is some association with increased adverse events (Nazir and Holdcroft, ). There are findings of chondrotoxicity with LAs alone and in combination with corticosteroids, including MPA (Braun et al, ; Dragoo et al, ; Rao et al, : Seshadri et al, ; Sherman et al, ). Although Ravnihar et al () reported contrary findings, judicious use in early disease is suggested.…”
Section: Addition Of Local Anaestheticmentioning
confidence: 99%